CD30 expression and survival in posttransplant lymphoproliferative disorders. (2nd June 2020) - Kinch, Amelie; Amini, Rose-Marie; Hollander, Peter; Molin, Daniel; Sundström, Christer; Enblad, Gunilla
Abstract: Background: Post-transplant lymphoproliferative disorder (PTLD) is a rare but life-threatening complication of transplantation. For refractory and relapsed PTLD new therapies are needed, such as the antibody-drug conjugate brentuximab vedotin that targets CD30. There is limited knowledge of CD30 expression in various subtypes of PTLD and its correlation to clinicopathological features. Therefore, we studied the expression of CD30 in PTLD following solid organ transplantation and correlated CD30 expression to PTLD subtype, Epstein-Barr virus (EBV)-status, intratumoral regulatory T-cells (Tregs), clinical features, and outcome. Methods: We included 50 cases of PTLD from a nation-wide study of PTLDs following solid organ transplantation in Sweden. The tumor biopsies were reevaluated, and clinical data were collected. CD30 expression on tumor cells was analyzed by immunohistochemistry with the clone Ber-H2. Thirty-one cases were stained with clone 236 A/E7 for detection of forkhead box protein 3 (FoxP3, a Treg biomarker). Results: The case series consisted of 6% polymorphic, 88% monomorphic, and 6% Hodgkin lymphoma-like PTLDs and 53% of the cases were EBV+. Overall, 70% (35/50) of the PTLDs were CD30+ (≥1% CD30+ tumor cells) and 30% (15/50) were CD30-. All polymorphic PTLDs ( n = 3) and Hodgkin lymphomas ( n = 3), 88% (14/16) of non-germinal center type of diffuse large B-cell lymphoma (DLBCL), and 75% (9/12) of T-cell PTLDs were CD30+ whereas all germinal center-type of DLBCL ( n = 5) and Burkitt type PTLD ( n = 2) were CD30-. CD30+ PTLD tended to be EBV+ more frequently ( p = .07) and occurred earlier posttransplant (2.1 vs. 8.2 years, p = .01) than CD30- PTLD. Type of transplant and localization of the tumor did not differ between the groups except that CNS engagement was more common in CD30- PTLD ( p = .02). CD30-status was not associated with presence of intratumoral Tregs or overall survival. Conclusion: Expression of CD30 varied with PTLD subtype. There was no association between CD30 and survival, regardless of subtype.